038 Development of Multidisciplinary Symptom Management Tools Using The ADAPTE Approach. (15th August 2013) - Harle, I; Bak, K; Molloy, S; Green, T
Abstract : Background: Evidence-based tools for symptom management were developed to assist healthcare providers in comprehensive assessment and appropriate management of symptoms. These evidence-based tools consist of comprehensive guides-to-practice, quick reference pocket guides, algorithms and smart phone apps. Objectives: The symptom management tools promote an interdisciplinary model of care that enables early identification and assessment of symptoms, appropriate documentation and communication regarding symptoms, optimal symptom management, and coordinated care throughout the illness trajectory. The tools are intended to be user-friendly, and are available in print, web and smart phone applications. Methods: The tools were developed by an interdisciplinary panel of healthcare providers using the ADAPTE guideline adaptation approach. This included a literature search for recent guidelines and systematic reviews, guideline appraisal using the AGREE tool and selection, and in some instances modification, of recommendations. Expert feedback was obtained and subsequently appropriate revisions were made. Results: The symptom management tools provide recommendations based on the best available evidence and expert consensus, for assessing, determining aetiology, diagnosing potential problems and for recommending non-pharmacological and pharmacological interventions. Implications for Guideline Developers/Users: The ADAPTE approach offers a comprehensive and rapid process of developing evidence-based tools for the cancer patient population. Following the global trend of creating user-friendly clinical guidance, the guides-to-practice, quick reference pocket guides, algorithms and smart phone apps are an innovative set of tools that are accessible to a diverse group of care providers, in a manner that would suit the individual's clinical needs.